PEMETAAN POHON BERNILAI BUDAYA BALI YANG LANGKA DI KOTA DENPASAR - Mahendra, Made Sudiana; Sukewijaya, I Made; Asmiwyati, I G. A.A. Rai (Bumi Lestari, 2011)
Plant has highly visible socio cultural role for Hindu people in Bali. Even though these plants were existed in the field, it was difficult to identify, monitor and update their existences. The objectives of this research are to identify the endangered socio cultural trees and to make a mapping system of the endangered socio cultural trees in Denpasar based on web. Mapping system was made using MySQL, PhP, Mapserver, Macromedia Dreamweaver and Mozila Firefox. As many as 39 species of socio cultural trees were categorized in endangered risk. The data inventory of cultural trees in Denpasar can be quickly accessed and effectively managed by Mapping Program.
Keywords: Balinese culture; endangered tree; Geographic Information System